The unreversible reduced but persistent activated NK and CD8+ T cells in severe/critical COVID-19 during omicron pandemic in China - Ling Qin; Xinmin Duan; Jay Zengjun Dong; Yue Chang; Yang Han; Yan Li; Wei Jiang; Hongwei Fan; Xiufeng Hou; Wei Cao; Huadong Zhu; Taisheng Li (Emerging Microbes and Infections)
As a hallmark of COVID-19 progression, lymphopenia alongside its subtle immune disturbance has been widely reported, but yet to be thoroughly elucidated. Aiming at exploring clinical immune biomarkers with accessibility in the current and acute omicron epidemic abrupted in China post-control era, we design a real-world prospective observation cohort in Peking Union Medical College Hospital to describe immunological, haematological profiles inducing lymphocyte subsets related to SARS-CoV-2 infection. In this COVID-19 cohort, we enrolled 17 mild/moderate (M/M), 24 severe (S) and 25 critical (C) patients. The dynamics of lymphocytes of COVID-19 demonstrated that the sharp decline of NK, CD8+, and CD4+ T cell counts was the main contributor to lymphopenia in the S/C group, compared to the M/M group. Expressions of activation marker CD38 and proliferation marker Ki-67 both in CD8+ T and NK cells were significantly higher in all COVID-19 patients than that in healthy donors, independent of disease severity. The subsequent analysis showed in contrast to the M/M group, NK and CD8+ T cell counts remained low-level after therapy in the S/C group. CD38 and Ki-67 expressions in NK and CD8+ T cells still stay at a high level, despite active treatment. Targeting relatively elderly patients with SARS-CoV-2 infection, severe COVID-19 features the unreversible reduction of NK and CD8+ T cells with persistent activation and proliferation, which assist clinicians in early recognizing and saving severe or critical COVID-19 patients. Given that immunophenotype, the new immunotherapy improving NK and CD8+ T lymphocyte antiviral efficiency should be considered.